THE ECONOMIC REASONS FOR THE DEVELOPMENT OF SOLAR GENERATION USING STANDALONE HYBRID POWER PLANTS IN ISOLATED ENERGY SYSTEMS - D. Arifulova (Publishing House of the State University of Management, 2018)
This article examines the significance of isolated energy systems for the Russian Federation. The dependence on expensive imported fuel in isolated energy systems and the need to develop alternative energy programs and energy efficiency of isolated systems have highlighted. The existing renewable energy sources in the territory of isolated energy systems have analysed and plans for their development have considered. In particular, an example of the implementation of energy-efficient autonomous hybrid power plants has presented by modernizing existing diesel power plants with the installation of solar panels.